Development and changes of Croatian social psychology: history and future perspectives - Čorkalo, Dinka; Ćubela Adorić, Vera (2005)
A development of Croatian psychology has been presented, with emphasis on the changes in research interest of academics and professionals, changes in methodology that has been used, and the changes in education of psychologist. A special attention has been devoted to the development of Croatian social psychology and related fields
ENG